2016
DOI: 10.1038/srep27433
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional high fatigue strength in Cu-15at.%Al alloy with moderate grain size

Abstract: It is commonly proposed that the fatigue strength can be enhanced by increasing the tensile strength, but this conclusion needs to be reconsidered according to our study. Here a recrystallized α-Cu-15at.%Al alloy with moderate grain size of 0.62 μm was fabricated by cold rolling and annealing, and this alloy achieved exceptional high fatigue strength of 280 MPa at 107 cycles. This value is much higher than the fatigue strength of 200 MPa for the nano-crystalline counterpart (0.04 μm in grain size) despite its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…It is previously reported that the σnormalf in Basquin equation is in scale with the tensile strength of materials 20 . So it is speculated that the strength variation (see Figure 6) between the M0 and M10 MGCs is responsible for the difference of σnormalf.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It is previously reported that the σnormalf in Basquin equation is in scale with the tensile strength of materials 20 . So it is speculated that the strength variation (see Figure 6) between the M0 and M10 MGCs is responsible for the difference of σnormalf.…”
Section: Resultsmentioning
confidence: 85%
“…It is previously reported that the σ 0 f in Basquin equation is in scale with the tensile strength of materials. 20 So it is speculated that the strength variation (see Figure 6) between the M0 and M10 MGCs is responsible for the difference of σ 0 f . On the other hand, the b is assumed to be correlated with the microstructure and damage mechanisms of materials.…”
Section: Tensile and Fatigue Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The material's crystal structure is of great significance to the research and development of modern advanced metal materials [1][2][3]. Micro-domain grains, texture, and others affect the formability of a part, which is directly related to the material's mechanical properties [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The methods based on qualitative manual analysis include orientation distribution analysis, inverse pole figure analysis, grain size analysis, etc. Based on this statistical approach, researchers observe specific features through images or statistical functions, thereby establishing a qualitative structure-performance relationship [2,[4][5][6][7][9][10][11][12][13]. Another method is to simulate and calculate the structure and properties of materials by establishing physical models, such as Visco-plasitic Self Consistant (VPSC), crystal plasticity finite element method [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%